IGEMS: The Consortium on Interplay of Genes and Environment Across Multiple Studies — An Update. (23rd December 2019) - Pedersen, Nancy L.; Gatz, Margaret; Finch, Brian K.; Finkel, Deborah; Butler, David A.; Dahl Aslan, Anna; Franz, Carol E.; Kaprio, Jaakko; Lapham, Susan; McGue, Matt; Mosing, Miriam A.; Neiderhiser, Jenae; et al.
Abstract: The Interplay of Genes and Environment across Multiple Studies (IGEMS) is a consortium of 18 twin studies from 5 different countries (Sweden, Denmark, Finland, United States, and Australia) established to explore the nature of gene–environment (GE) interplay in functioning across the adult lifespan. Fifteen of the studies are longitudinal, with follow-up as long as 59 years after baseline. The combined data from over 76, 000 participants aged 14–103 at intake (including over 10, 000 monozygotic and over 17, 000 dizygotic twin pairs) support two primary research emphases: (1) investigation of models of GE interplay of early life adversity, and social factors at micro and macro environmental levels and with diverse outcomes, including mortality, physical functioning and psychological functioning; and (2) improved understanding of risk and protective factors for dementia by incorporating unmeasured and measured genetic factors with a wide range of exposures measured in young adulthood, midlife and later life.